Estrategias lúdicas para fortalecer la comprensión de ejercicios matemáticos en estudiantes del subnivel de educación básica media - Triviño Baren , Fanny Janet (2025)
The teaching of mathematics is recognized as an essential pillar where the foundations for problem-solving, logical thinking, and abstract reasoning are established. In Ecuador, difficulties in the comprehension of mathematical exercises persist, as a result of traditional methodologies based on memorization and the scarce application of innovative resources. Faced with this reality, the present study aims to analyze ludic strategies for the comprehension of mathematical exercises in students of the middle basic level at Cotacachi School. The central problem lies in the low use of games and pedagogical dynamics in the teaching of mathematics, which generates demotivation and low performance. The analysis of information was carried out through bibliographic and historical research, adopting a mixed-method approach, with a descriptive type of research and a non-experimental design. Work was done with a population of 25 students, 2 teachers, and 1 educational psychologist. Surveys, interviews, and observation were applied, which allowed the triangulation of information. The results show that most students (76%) express a liking for mathematics, although 60% state that they have never worked with games in classes. Likewise, 72% consider that mathematical problems are easier when related to real situations, and 92% indicate that they prefer to learn through group games. The teachers and the specialist interviewed recognize the value of ludic strategies to motivate and facilitate comprehension, but they point out limitations such as lack of resources, scarce training in innovative pedagogies, and insufficient family support. The observation corroborated that classes maintain a traditional approach, with games applied sporadically. The proposal of this research suggests the implementation of innovative dynamics that allow students to build meaningful learning, strengthen logical reasoning, and improve their academic performance.